Higher Education in the Context of Modern Civilizational Gaps. Review of the Book by E. Galazhinsky "Conversations about Difficult Things. Management Practices and Reflections" - Elena V. Khakhalkina (Вопросы образования)
The book “Conversations about the difficult” is a publication of blog entries by the rector of the National Research Tomsk State University Eduard V. Galazhinsky in 2022-2023 and several interviews with the author about current trends in the development of higher education in Russia and the world. The review raises questions about the role and place of technological progress in the learning process, the model of a new generation university in the logic of the Fourth Industrial Revolution, and changing approaches to knowledge as one of the educational tools and products. Special attention is paid to the assessment of the Bologna system, its positive and negative impact on the Russian higher education system, the consequences of Russia's withdrawal from it, and the civilizational gaps of modernity against the background of geopolitical realities. In the reviewed book the classical university with its centuries-old traditions and their organic intertwining with the innovations of the time considers as one of the key elements of an effective model of higher education. According to the author of the review, this book can be useful to anyone who is interested in the development of higher education in Russia, its achievements, difficulties and prospects.